Ultra-Processed Food in an Inpatient Mental Health Setting - Anthony Onjewu; Ed Silva; Anthony Onjewu (BJPsych Open, 2025)
Aims: The consumption of ultra-processed food (UPF) is associated with many adverse health outcomes including cardiometabolic disorders, mental health disorders and mortality.